Middle-school students' reasoning about alternative hypotheses in a scaffolded, software-based inquiry investigation - Kyza, Eleni A. (My University, 2009)
The examination of alternative hypotheses can initiate students into scientific practices and equip them with scientific literacy skills that will help them participate in ongoing debates involving complex socio-scientific problems. Hypothesis testing, in which the examination of alternative hypotheses is situated, has received much attention in the literature. However, the topic of alternative hypotheses has not been examined as extensively in scaffolded data-rich instructional interventions. This article contributes to that body of knowledge by reporting on middle-school students' inquiry practices as they relate to considering alternative hypotheses of their data. Specifically, the article reports a multiple-case study examining six pairs' reasoning as they try to solve a data-rich, scientific problem, scaffolded by the software investigation, the task setup, and the teacher. The students' generation and testing of alternative hypotheses was examined through students' discourse, actions, inquiry products, and interactions with their teacher and peers. Pre-post assessment analyses showed statistically significant learning gains while the analyses of the students' inquiry discourse and actions indicated that the scaffolding contributed to students' inquiry. However, several epistemological problems surfaced relating to students' perception of the usefulness of examining and communicating alternative explanations. These findings indicate the importance of epistemologically targeted discourse alongside guided inquiry experiences, and underline the need for further examination of appropriate scaffolding to support students' scientific reasoning processes.
Keywords: Literacy; Communication; Students